Senses of Community in Finnish Nonbinary Lives : Solidarity and Trans Care on Social Media Platforms - Kukko, Saarni (My University, 2026)
The topic of this thesis is senses of community on online platforms. In this thesis, I examine the complex ways Finnish nonbinary people experience online communities and sense of community in online spaces. I approach the topic with data consisting of sixteen social media diaries and sixteen interviews based on these diaries. All participants were Finnish nonbinary adults. The data for this thesis is from the Intimacy in Data-Driven Culture research project. I approach the qualitative dataset through thematic analysis. The data was collected during the COVID-19 pandemic and during a time of heated discussion about the revision of the Trans Act in Finland; therefore, I find it important to discuss the juridical, political, historical, and medical standing of nonbinary and trans people in Finland. Moreover, this thesis is an extension of research on trans and queer communities on social media. I approach the data with conceptualisations of community, solidarity, and trans care as the theoretical framework. Through thematic analysis I illustrate how diversely sense of community is experienced on social media platforms and contemplate on the role of shared identity in communities. Furthermore, I contend that solidarity and trans care are practiced through both social media interactions and online community engagement. I suggest that further research concerning the intersections of identity and sense of community is needed.
Keywords: community; nonbinary; online community; sense of community; social media; solidarity; trans care